PENGARUH GOOD CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL - Ariedina Ariedina; Liana Susanto (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of the independent variable which are proportion of independent commissioner, board size, audit committee’s meeting frequency, audit committee’s size and profitability on dependent variable, intellectual capital disclosure. The sample on this research is limited on manufacturing companies listed on Indonesia Stock Exchange during the year 2017-2019. Data processing techniques examined by logistic regression and using Eviews 12 SV to process the data. The result of this research was board size and audit committee’s size have significant and positive impact on intellectual capital disclosure,while proportion of independent commissioner, audit committee’s meeting frequency,and profitability have no significant impact on intellectual capital disclosure.